Gd2O3 nanoparticles modified wave‐like carbon host derived from soybean residue as cathodes in lithium–sulfur batteries. (8th February 2022) - Yan, Yinglin; Jing, Wei; Yang, Yuanyuan; Fan, Chaojiang; Shi, Mangmang; Ren, Bing; Zou, Yiming; Feng, Zufei; You, Caiyin; Deng, Qijiu; Yang, Rong
Summary: Many kinds of nanostructured metal oxides were introduced in cathodes of Li–S batteries for high sulfur utilization and effective confinement for polysulfides. Herein, Gd2 O3 nanoparticles modified wave‐like carbon host, which are derived from soybean residue by activation and pyrolysis processes. After the activated soybean residue derived carbon (ASC) host modified by Gd2 O3 nanoparticles, the ASC‐Gd was integrated with sulfur by melting method and then used as cathode in lithium–sulfur (Li–S) batteries. According to the electrochemical results of ASC‐Gd/S cathode, a high initial discharge capacity (1343 mAh g −1 at 0.1 C) and improved cycling stability were exhibited, which was attributed to the strong adsorption ability for polysulfides and ultrahigh specific surface area of the ASC. As a result, the Gd2 O3 nanoparticles modified wave‐like biomass carbon was a promising host material of Li–S batteries with high performances. Abstract : Gd2 O3 nanoparticles were attached in wave‐like hierarchical porous carbon pyrolyzed from soybean residue. Gd2 O3 /carbon composite integrated with sulfur was utilized as cathode in Li–S battery. The carbon matrix with ultra‐high specific surface area is beneficial for the specific capacity. The Gd2 O3 nanoparticles showed significant adsorption ability for polysulfides, which improved the cycling stability.